The Effect of Compensation, Work Motivation on Job Satisfaction and Employee Performance at PT. Cremonapratama Total Engineering Bengkulu City - Amlianto, Aryo Kadman; Arini , Eti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This Job satisfaction is an expression of a person’s feelings or attitude towards his work, while employee performance is the end result of maximum employee work to achieve company goals and objectives for progress and achieving the company’s goals. The research objective is to determine the effect of compensation on job satisfaction and employee performance. This type of research is quantitative research, carried out at PT. Cremonapratama Total Engineering Bengkulu City in March 2023 until completion. Data collection using questionnaires and data analysis using multiple linear regression models, determination analysis and hypothesis testing, with the help of SPSS software. The results showed that compensation has a significant effect on employee job satisfaction. Work motivation has a significant effect on job satisfaction. Compensation and work motivation have a significant effect on employee job satisfaction. Compensation has a significant effect on employee performance. Work motivation has a significant effect on employee performance. Compensation and work motivation have a significant effect on employee performance.